Effects of Huangqi Liuyi Decoction in the Treatment of Diabetic Nephropathy and Tissue Distribution Difference of its Six Active Constituents Between Normal and Diabetic Nephropathy Mouse Models - Wang, Qun; Shi, Ya; Wu, Zengguang; Song, Xinli; Luo, Jinfang; Yang, Hong; Chen, Xiaolan; Liu, Xingde (Frontiers in Pharmacology, 2022)
The purpose of this study was to investigate the effects of Huangqi Liuyi decoction extract (HQD) on diabetic nephropathy (DN), and the tissue distribution difference of six main active ingredients of HQD between normal and DN mouse models. DN mice were administered HQD for 12 weeks to investigate its efficacy in the treatment of DN. Liquid chromatography-tandem mass-spectrometry (HPLC-MS/MS) was used to analyze the tissue distribution of the six active ingredients of HQD in normal and DN mice, including astragaloside IV, calycosin-7-O-β-D-glucoside, calycosin glucuronide, ononin, formononetin, and glycyrrhizic acid. DN mice treated with HQD showed significantly decreased fasting blood glucose (FBG), 24-hour urinary protein (24 h U-Alb), blood urea nitrogen (BUN), serum creatinine (Scr), and triglyceride levels (TG) (P < 0.05). Moreover, there were no significant differences in pharmacodynamics between HQD and Huangqi Liuyi decoction. Treated mice also had decreased expression of collagen I, ɑ–smooth muscle actin (ɑ-SMA), and vimentin; and upregulated expression of E-cadherin in their kidneys. Compared with normal mouse, distributions of six ingredients in the liver, heart, spleen, lung, kidney, stomach, small intestine, brain, and muscle in DN mouse were different from those in the normal group. The results indicated that the HQD could be used for the treatment of DN and to improve renal function, and the pathological state of diabetic nephropathy could affect tissue distribution of HQD active ingredients in mouse.